Institutional environment, ownership structure and firm-specific information: Evidence from a transitional economy - Bùi, Thị Kim Dung (Taylor and Francis Online, 2022)
This study examines the relationship between ownership structure and stock price informativeness in a transitional economy characterized by an underdeveloped corporate governance system. Using a sample of 322 publicly listed companies in Vietnam covering a 10-year period from 2009 to 2018, we evaluate how national governance quality affects the impact of ownership type on stock price informativeness. We find the evidence that government-owned firms tend to have higher synchronous (lower informative) stock prices, whereas the opposite is true for the foreign-owned firms. Furthermore, the stock price informativeness of government-owned firms is higher when there is an increase in national governance quality. This study finds no significant difference in governance quality benefits between foreign-controlled and non-foreign firms. These findings suggest that the institutional channel plays an important role in determining the informativeness of the stock prices of government-controlled firms, especially in transitional economies.